Achieving high survival rate following cryopreservation after isolation of prepubertal mouse spermatogonial cells - Alipoor, Firooz Jannat (Springer US, 2009)
PURPOSE: Isolating spermatogonia cells with high purity and viability and achieving better survival rate following cryopreservation METHODS: Isolating the cells by Magnetic Activating Cell Sorting (MACS) method using anti CD49f (α6 integrin) antibody and Dynabeads and freezing in DMSO-based freezing mediums containing three different FBS concentrations of 50%, 60% and 70%. RESULTS: The mean (±SD) purity of the isolated cells was 92.52 ± 3.57 (range 92.43–98.25). The cells frozen in group I, II and III had mean 39.60 ± 1.48 (range 37.98–41.62), 89.05 ± 3.83 (range 80.83–90.33) and 90.52 ± 1.71 (range 89.07–92.52) viability, respectively. CONCLUSION: Higher viable cell counts and purity can be attained by the use of α6 integrin and magnetic beads. After the thawing of spermatogonial cells, optimum viability was achieved in freezing media containing 60% FBS.